Differential Protein Expression between Type 1 Diabetic Cataract and Age-Related Cataract Patients - Qianqian, Y; Yong, Y; Zhaodong, C; Yonghui, T; Jun, S; Yuzheng, H (Folia biologica, 2015)
Diabetes has become one of the major diseases affecting human health. Diabetic cataracts (DCs) are considered a common complication in diabetic patients. The present study investigated differences in lens proteomic profiles between DCs and age-related cataracts (ACs) to determine the mechanism underlying the formation of DCs. Intrasurgical samples were collected from eight DC patients and 12 AC patients, and lens proteins were extracted by lysis and separated using two-dimensional gel electrophoresis (2-DE). The electrophoretic bands were analysed using PD-Quest software 8.0.1. Differentially expressed proteins were identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) and peptide mass fingerprinting combined with protein database searching. In the 2-DE maps, the DC and AC lens proteins migrated in the region of pH 5-9 with a relative molecular weight (RMW) of 14-97 kDa, whereas the RMW of more abundant crystallin was 20-31 kDa. Approximately three protein spots with differential intensity were detected. Two crystallin proteins (αB and βB1) were identified using MALDI-TOF-MS. Proteomic analysis of the crystalline humour is feasible, and the proteins can be well separated; moreover, differentially expressed lens proteins can be analysed using 2-DE and mass spectrometry to compare DC and AC. The present results indicate that the αB and βB1 crystallins may accelerate the development of DCs. These techniques offer new avenues for mechanistic evaluation and future prevention or therapy of DCs.
Keywords: oční čočka; dospělí; 2D gelová elektroforéza; proteom; Adult; beta-Crystallin B Chain; Aging; Proteome; katarakta; Lens, Crystalline; lidé; Gene Expression Profiling; alfa-krystaliny - řetězec B; stanovení celkové genové exprese; hmotnostní spektrometrie; Eye Proteins; Cataract; Diabetes Mellitus, Type 1; regulace genové exprese; oční proteiny; beta-krystaliny - řetězec B; stárnutí; Electrophoresis, Gel, Two-Dimensional; Diabetes Complications; Mass Spectrometry; alpha-Crystallin B Chain; lidé středního věku; Gene Expression Regulation; komplikace diabetu; Middle Aged; diabetes mellitus 1. typu; Humans